Spectral behavior of tree species of individuals of the families Fabaceae and Myrtaceae, present in the Botanical Garden of the Federal University of Santa Maria (UFSM) - Fantinel , Roberta Aparecida; Benedetti , Ana Caroline Paim; Cardoso , Claire Delfini Viana; Sá, Renato Giovani Chaves de; Duarte , Natália Melos; Fernandes , Vinícius Henrique (Seven Editora, 2024)
The objective of this study was to analyze the spectral behavior of individuals of six species present in the Botanical Garden of the Federal University of Santa Maria. The individuals were randomly chosen, taking into account three species belonging to the Myrtaceae families and three species belonging to the Fabaceae family. The leaves selected by means of visual diagnosis were green and healthy, with no presence of symptoms of pest or disease on the adaxial or abaxial surface of the leaf. The spectral behavior of the leaves was recorded with the FieldSpec® HandHeld spectroradiometer sensor, which acts in the range between the wavelengths of 325nm to 1075nm of the electromagnetic spectrum. In the SAMS application, the reflectance factor (ρ) graphs were generated as a function of the wavelength (nm) for each species. The differences between the spectral behaviors of the species were tested by analysis of variance (ANOVA) and Tukey's test, using the R software. It was observed that Psidium guajava and Eugenia involucrata differ from each other regarding the means of reflectance in all visible spectral bands. The species Acca sellowiana and Psidium guajava differ from each other in the blue, red and near-infrared bands. For the other comparisons, no significant differences were found. For individuals of the Fabaceae family, the species Libidibia ferrea differed from the species Senna multijuga and Cassia leptophylla in the three bands of the visible spectrum. Libidibia ferrea differed from Cassia leptophylla in the near-infrared spectrum. The spectroradiometer proved to be efficient in the analysis and identification of differences between the species of the Myrtaceae and Fabaceae families. DOI:https://doi.org/10.56238/sevened2024.004-015